Convergence substitution for paralysed horizontal gaze. Issue 3 (March 1995) - Beigi, B; O'Keeffe, M; Logan, P; Eustace, P
Abstract : Three patients with paralysed horizontal gaze are presented. Involuntary use of convergence to assist horizontal gaze was noted as a late feature. All patients showed (1) unilateral or bilateral horizontal gaze palsy (two patients had one and a half syndrome, the other had bilateral nuclear sixth nerve palsies), (2) adduction of both eyes on attempted gaze into the paralysed field, (3) miosis which coincided with adduction. Convergence substitution should be considered in the differential diagnosis of gaze induced strabismus.